Diet-Derived Gallated Catechins Prevent TGF-β-Mediated Epithelial-Mesenchymal Transition, Cell Migration and Vasculogenic Mimicry in Chemosensitive ES-2 Ovarian Cancer Cells. (2nd January 2021) - Sicard, Audrey-Ann; Dao, Tiziana; Suarez, Narjara Gonzalez; Annabi, Borhane
Abstract: Background: Transforming growth factor (TGF)-β triggers ovarian cancer metastasis through epithelial-mesenchymal transition (EMT). Whereas drug design strategies targeting the TGF-β signaling pathway have been envisioned, the anti-TGF structure:function aspect of chemopreventive diet-derived catechins remains unexplored. Aim: We assessed the effects of eight catechins on TGF-β-mediated cell migration and induction of EMT biomarkers, as well as on In Vitro vasculogenic mimicry (VM), a process partly regulated by EMT-related transcription factors. Results: TGF-β-mediated phosphorylation of Smad-3 and p38 signaling intermediates was more effective in a chemosensitive ES-2 ovarian cancer cell line but was inoperative in cis-platinum- and adriamycin-chemoresistant SKOV-3 ovarian cancer cells. Increases in cell migration and in gene/protein expression of EMT biomarkers Fibronectin, Snail, and Slug were observed in ES-2 cells. When VM was assessed in ES-2 cells, 3D capillary-like structures were formed and increases in EMT biomarkers found. Catechins bearing the galloyl moiety (CG, ECG, GCG, and EGCG) exerted potent inhibition of TGF-β-induced cell migration as well as EMT, and inhibited VM, in part through inhibition of Snail and matrix metalloproteinase-2 secretion. Conclusions: Our data suggest that diet-derived catechins exhibit chemopreventive properties that circumvent the TGF-β-mediated signaling which contributes to the ovarian cancer metastatic phenotype.